La cultura organizacional y la eficiencia y eficacia en la toma de decisiones en las medianas y pequeñas empresas de calzado del distrito el porvenir, provincia de Trujillo. departamento de la libertad. 2006 - Salcedo Dávalos, Rosa Amable (2007)
We live a historical moment of deep, quick and global transformations and we are beginning or only a new century, but a new millennium, being witness of the most impressive changes in the world in all the environments of the culture. The culture of an organization describes the part of its internal atmosphere that incorporates the series of suppositions, beliefs and values that to share the members of the organization and that they use to guide its operation. The organizational cultures that are strong, strategically correct and adaptive they have positive repercussions for the economic acting of the long term organization. Several they are the forms that the members of an organization use the culture: • To support the commercial strategy of the organization • To prescribe acceptable measures that the integral interactúen with external publics • To make decisions of personal • To establish approaches for the acting • To guide the character of the interpersonal relationships inside the company. • To choose the correct administrative styles. The investigation is centered in giving answer to the following query: Are they related among if the organizational culture and the efficiency and effectiveness in the taking of decisions and how to improve the organizational culture of the members of the medium and small companies of footwear of the district of the Future county of Trujillo department of The Freedom 2006? For the realization of the study of he/she has taken as sample of 10 companies (05 small and 05 medium companies) the same ones that have been selected by means of sampling non probabilístico. In the investigation you concludes that the organizational culture this related one positively with the efficiency and effectiveness in the taking of decisions in the medium and small footwear companies.